2006
DOI: 10.1186/cc5067
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value and prognostic implications of serum procalcitonin after cardiac surgery: a systematic review of the literature

Abstract: Introduction Systemic inflammatory response syndrome is common after surgery, and it can be difficult to discriminate between infection and inflammation. We performed a review of the literature with the aims of describing the evolution of serum procalcitonin (PCT) levels after uncomplicated cardiac surgery, characterising the role of PCT as a tool in discriminating infection, identifying the relation between PCT, organ failure, and severity of sepsis syndromes, and assessing the possible role of PCT in detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(55 citation statements)
references
References 69 publications
2
47
0
6
Order By: Relevance
“…The use of serial measurements instead of a single observation reinforces the predictive power of PCT and reduces the risks of false negatives and false positives [3943]. The same considerations are valid for the use of PCT in the investigation of suspected postoperative sepsis [44], which is currently performed after many types of surgical procedures [4549]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of serial measurements instead of a single observation reinforces the predictive power of PCT and reduces the risks of false negatives and false positives [3943]. The same considerations are valid for the use of PCT in the investigation of suspected postoperative sepsis [44], which is currently performed after many types of surgical procedures [4549]. …”
Section: Discussionmentioning
confidence: 99%
“…C-reaktif protein (CRP) genellikle yüksektir. Kardiyak cerrahi sonrası gelişen infeksiyonların takibinde prokalsitoninin CRP'ye üstün olduğuna ilişkin bir çalışma mevcuttur; ancak mediyastenit olgularına özel bir irdeleme yapılmamıştır (11). Mediyastenit tanısında kan kültüründe üreme olma sıklığı etkene göre değişmektedir.…”
Section: Tanıunclassified
“…However, it must be considered that the same absolute values of PCT cannot be used in all circumstances. It has been reported that PCT levels are higher in surgical compared to medical patients [12], and elevated PCT can also be present without infection, in conditions such as trauma [13] and surgery [14] or after cardiac arrest [15]. There is some evidence that evaluating PCT kinetics may be superior to absolute values [12, 16].…”
Section: Introductionmentioning
confidence: 99%